Genetic determinants of Vitamin C content in higher plants - Fenech-Torres, Mario; Amorim-Silva, Vitor; Smirnoff, Nicholas; Valpuesta-Fernández, Victoriano; Botella-Mesa, Miguel Ángel (My University, 2018)
Ascorbic acid (AsA, VitC) is the most abundant water-soluble antioxidant in plants and it plays a plethora of biological roles including resistance to abiotic stress. Hence, including VitC as a trait to improve in breeding programs is not only a way to enhance food quality but also to increase resistance to expected environmental alterations due to global change like drought, salinity or heat. Although all components of the Smirnoff-Wheeler pathway of AsA in plants are known, little information is available about how their regulation at the biochemical and cellular levels is. We have generated a number of molecular tools such as tagged constructs, stable transgenics and mutant lines with the aim of getting detailed information about how this pathway operate in plants. We will present data on protein localization, interaction among different components and their role in affecting VitC levels using a heterologous system such as Nicotiana bethamiana. This research was supported by a grant from the Spanish Ministerio de Educación, Cultura y Deporte para la formación del Profesorado Universitario (FPU014/01974), as well as by a project funded by the Spanish Ministerio de Ciencia e Innovación (BIO2014-55380R; BIO2014-56153-REDT). We also acknowledge the support by the Plan Propio from University of Malaga, Campus de Excelencia Internacional de Andalucía.
Keywords: Biología molecular vegetal - Congresos; Abiotic stress; Vitamin c; Arabidopsis; Plant